Local Wisdom Addressing Global Challenges: Integrating Ita Wotu Nusa Values into the Love Based Curriculum (KBC) at Islamic Junior High Schools in East Seram Regency - Farid Ma'ruf Suwakul (al-Iltizam: Jurnal Pendidikan Agama Islam, 2025)
In the era of globalization and digital disruption, secondary educational institutions such as Madrasah Tsanawiyah (Islamic Junior High Schools) face increasing exposure to foreign cultural influences that risk alienating younger generations from their cultural identity, particularly in Indonesia's 3T regions (underdeveloped, frontier, and outermost areas). This study aims to formulate a model for integrating the local wisdom of East Seram Regency namely the Ita Wotu Nusatutun philosophy, which emphasizes kinship, social cohesion, and mutual cooperation, and the Sasi tradition, which promotes environmental conservation into the paradigm of the Love-Based Curriculum (Kurikulum Berbasis Cinta/KBC) implemented in Islamic Junior High Schools in East Seram Regency. The Love-Based Curriculum is a humanistic pedagogical approach grounded in compassion that seeks to foster students' affective development. Employing a qualitative approach with a descriptive-analytical case study design, data were collected through in-depth interviews with school principals, Islamic Religious Education (IRE) teachers, and customary leaders, complemented by document analysis of curriculum drafts and teaching modules from three partner Islamic Junior High Schools in East Seram Regency during 2026. Data were analyzed thematically using an interactive coding process. The findings reveal that a curriculum excessively oriented toward meeting global cognitive and administrative standards contributes to a phenomenon of cultural fracture among adolescent students. As a strategic response, this study proposes the Ita Wotu Love-Based Curriculum Framework, a pedagogical reconstruction model that operationalizes the value of mutual cooperation into socio-pedagogical behavioral indicators while transforming the Sasi tradition into an eco-theological educational praxis. The study concludes that local wisdom should not be viewed merely as a cultural heritage of the past but as a transformative curricular instrument capable of decolonizing Islamic secondary education while nurturing graduates with strong character and cultural resilience in the face of globalization.